Critical time of nitrogen application during panicle initiation on the yield of two Malaysia rice cultivars (Oryza sativa L.) - A. Bah,; Syed Rastan, Syed Omar; Abdul Rahim, Anuar; Mohd Hanif, Ahmad Husni (Universiti Putra Malaysia Press, 2009)
Nitrogen is the most limiting nutrient in rice production. N fertilizer is susceptible to losses when the time of application does not match with period of crop demand. A glasshouse experiment was conducted to determine the critical time of nitrogen fertilizer application at panicle initiation on grain yield of two Malaysian rice cultivars (MR219 and MR232). The experiment consisted of five N treatments applied each at 60 kg ha-1 at 45 (NI), 50 (N2), 55 (N3), 60 (N4) and 65 (N5) days after seeding (DAS) with five replications. Prior to this stage, a total of 75 kg N ha-1 was applied during vegetative growth stage (at 15 and 35 DAS). Plant physiological parameters such as height, SPAD value and LAI showed statistical difference among some treatments. Application of N also resulted in an increase in plant biomass. The results demonstrate that the split application of fertilizer N at PI stage (55 DAS) significantly increased percentage of filled grains, 1000-grain weight and total grain yield. Incorrect timing of N application (65 DAS) at P1 stage, drastically reduced rice yield to approximately 39% for MR2 19 and 17% for MR232. Farmers should be advised to apply N between 50 DAS and 55 DAS, even though application of N at 55 DAS was far better than 50 DAS in terms of yield parameters.